CRITICAL THOUGHTS ON THE DISCOURSE OF “CIVILISATION OF MORALITY” - Abdüllatif TÜZER (Fırat University, 2019)
There is a well-known judgement frequently expressed in the works of Muslim authors: the Western world is undoubtedly powerfull and advanced in science and technology but poor, degenerated and regressed in morality and spirituality. Two consequences can be derived from this judgement: 1) Only the science and technology of the West, not its morality, can be imported; 2) the West is a civilisation of science and technology; whereas the East sublimed thanks to Islam is a civilisation of morality and spirituality. Hence, though the West is advanced in science and technology, it is not superior than the East in morality. Morality and spirituality is a distinguishing mark of the East and hence, in this respect, it is superior than the West. However, the claim that the Muslim East is a civilisation of morality and spirituality to the extent that it can serve as a model for the West is, when it is subjected to the philosophical criticism, quite naive and weak. History of ethics is full of discussions as to which, i